Современные тенденции в управлении; Основы управления предприятием - Андреев Г. И. Григорий Иванович; Волчихин В. И. Владимир Иванович; Миронов В. А. Вячеслав Александрович; Тихомиров В. А. Валерий Александрович (2005, 2005)
Авт. и ред. указ. на обороте тит. л.